Methods of allergen detection based on DNA analysis - Słowianek, Marta; Majak, Iwona (Wydawnictwo Politechniki Łódzkiej, 2011)
Many allergens, such as hazelnut, peanut, charlock, celery, sesame, lupine, walnut, almond, macadamia nut, hickory, pistachio, wheat gliadins, may be present in food products, however, undeclared or as unintentional additives. Due to the growing number of allergic reactions, it is crucial to have fast, reliable methods of allergen detection in processed food products. This review summarizes the recent methods of allergen detection in food products based on PCR reactions, namely PCR-ELISA, Real-time PCR, PCR-PNA-HPLC, Duplex PCR and Multiplex Real-time PCR, describing their principles, applications, detection limits, drawbacks and advantages.